GINGER PRODUCTION IN MORRETES TOWN, PARANÁ STATE - ELPO, Eliane Rose Serpe; NEGRELLE, Raquel Rejane Bonato; RÜCKER, Neusa Gomes de Almeida (Scientia Agraria, 2008)
The ginger production at the Morretes Municipality / Parana State evidencing the congruence and incongruity of the observed procedures taking into consideration what is reported on literature as being proper for this crop is presented. Field research, participatory observation and interviews were used to collect data. The main problems registered were: absence of soil analyses; inadequate acquirement and storage of propagation units; inadequate and intense use of agro toxics diminishing export opportunities, plagues and diseases associated with inadequate cultivation procedures and management; low microbiological quality of the water used for irrigation and to clean the fresh rhizomes, and absence or lack of quality of the storage room. Transference of technical information to producers, including those relating to application of good agricultural practices of ginger crop, is recommended.